2009
DOI: 10.1099/mic.0.023531-0
|View full text |Cite
|
Sign up to set email alerts
|

Citrate-mediated iron uptake in Pseudomonas aeruginosa: involvement of the citrate-inducible FecA receptor and the FeoB ferrous iron transporter

Abstract: In an attempt to identify components of a ferric citrate uptake system in Pseudomonas aeruginosa, a mutant library of a siderophore-deficient strain (IA614) was constructed and screened for defects in citrate-promoted growth in an Fe-restricted medium. A mutant disrupted in gene PA3901, encoding a homologue of the outer-membrane ferric citrate receptor, FecA, of Escherichia coli (FecAE.c.), was recovered and shown to be deficient in citrate-promoted growth and citrate-mediated Fe uptake. A mutant disrupted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
100
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(102 citation statements)
references
References 68 publications
0
100
2
Order By: Relevance
“…This suggested that our two-component system, comprising a cytoplasmic response regulator (bqsR) and a sensor histidine kinase (bqsS) and identified by its conserved kinase domain and its predicted localization to the inner membrane, was sensing extracellular Fe(II). To test this, we used qRT-PCR to measure the expression of bqsR and bqsS in response to Fe(II) shock in the wild-type (WT) strain and in strain feoB::MAR2xT7 [which has a severe defect in Fe(II) uptake across the cytoplasmic membrane (31,32,61)]. If the cells were sensing extracellular Fe(II), we anticipated that bqsR and bqsS expression would be the same in both the wild type and the feoB mutant.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggested that our two-component system, comprising a cytoplasmic response regulator (bqsR) and a sensor histidine kinase (bqsS) and identified by its conserved kinase domain and its predicted localization to the inner membrane, was sensing extracellular Fe(II). To test this, we used qRT-PCR to measure the expression of bqsR and bqsS in response to Fe(II) shock in the wild-type (WT) strain and in strain feoB::MAR2xT7 [which has a severe defect in Fe(II) uptake across the cytoplasmic membrane (31,32,61)]. If the cells were sensing extracellular Fe(II), we anticipated that bqsR and bqsS expression would be the same in both the wild type and the feoB mutant.…”
Section: Resultsmentioning
confidence: 99%
“…When pyoverdine-bound Fe(III) enters the periplasm via TonB-dependent outer membrane transporters, iron is thought to be released from the pyoverdine complex via reduction facilitated by its binding to an inner membrane ABC transporter, allowing Fe(II) to enter the cytoplasm (59). In addition, P. aeruginosa can excrete citrate, which also chelates Fe(III), albeit with lower affinity than siderophores, causing the iron to enter the cytoplasm as Fe(II) through a different TonB-dependent porin and the G-protein-like transporter FeoB (31,32). Pseudomonas also contains two heme uptake systems whose outer membrane receptors are HasR and PhuR, which are energized by an ABC transporter and TonB, respectively (39).…”
mentioning
confidence: 99%
“…In support of this idea, genes encoding the ferrous iron and heme uptake systems are consistently expressed by P. aeruginosa growing in the CF lung (33,35). P. aeruginosa acquires ferrous iron via the Feo system, a G-protein-like transporter of ferrous iron (36)(37)(38)(39), and mediates heme acquisition via at least two systems: Phu (Pseudomonas heme uptake) and Has (heme assimilation system) (40). Once internalized, heme is bound by the cytoplasmic heme chaperone PhuS and delivered to an iron-regulated heme oxygenase (hemO), which degrades heme to iron, CO, and biliverdin (BVIX) (41).…”
mentioning
confidence: 90%
“…Ϫ mutant allowed for identification of the FecA outer membrane transporter and its role in citrate-mediated iron import (40), and high-affinity import of iron(III) dicitrate through FecA is well established in Escherichia coli and several other bacteria (7). As the DC3000 genome contains a fecA homolog (PSPTO_1207), DC3000 might pirate iron(III) dicitrate from host fluids.…”
Section: Pvdmentioning
confidence: 99%